2020
DOI: 10.1016/j.ajhg.2020.08.019
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Rare Epigenetic Variation in 23,116 Human Genomes Identifies Disease-Relevant Epivariations and CGG Expansions

Abstract: There is growing recognition that epivariations, most often recognized as promoter hypermethylation events that lead to gene silencing, are associated with a number of human diseases. However, little information exists on the prevalence and distribution of rare epigenetic variation in the human population. In order to address this, we performed a survey of methylation profiles from 23,116 individuals using the Illumina 450k array. Using a robust outlier approach, we identified 4,452 unique autosomal epivariati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 57 publications
5
54
0
Order By: Relevance
“…In addition, folate stress induces MiDAS or γ-H2AX foci, a marker of DSBs, at many genomic loci in normal human cells ( Kumari et al, 2009 ; Garribba et al, 2020 ), suggesting that there are also several common folate-sensitive fragile sites that are as yet uncharacterized. Furthermore, a recent study of epigenetic variation in the human genome suggests the existence of at least 19 rare, long, and silenced CGG repeat tracts that could well also be fragile ( Garg et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, folate stress induces MiDAS or γ-H2AX foci, a marker of DSBs, at many genomic loci in normal human cells ( Kumari et al, 2009 ; Garribba et al, 2020 ), suggesting that there are also several common folate-sensitive fragile sites that are as yet uncharacterized. Furthermore, a recent study of epigenetic variation in the human genome suggests the existence of at least 19 rare, long, and silenced CGG repeat tracts that could well also be fragile ( Garg et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the cause of the disease may be outside the four base pair genetic code. Human disease can also be caused by rare epigenetic variation (epivariation, epimutations) [267], defined as an alteration in DNA methylation, irrespective of their underlying etiology (sporadic events such as imprinting anomalies [268] or sequence variation [269]). Although the contribution of epivariations to mitochondrial disorders remains unexplored, recent studies reported enrichment of de novo epivariation in congenital disorders and neurodevelopmental disorders, followed by altered gene expression [270,271].…”
Section: Non-mendelian Inheritancementioning
confidence: 99%
“…This work suggests that epivariants may underlie a fraction of human disease that would be missed with purely genetic sequence-based approaches. This study provides a broad overview of rare epigenetic changes in the human genome, giving insight into the underlying origins and consequences of epivariations, potentially altering the methylation pattern related to human diseases [ 163 ]. In this light, it is important to distinguish the constitutional secondary epimutations that cause diseases from the common epigenetic variants, usually influenced by ethnicity and caused by non-pathogenic natural adaptive mechanisms in humans [ 164 ].…”
Section: Cis -Acting Factors Causing Secondary Epimutations: Historical Evidencementioning
confidence: 99%